The Direction of Desire John of the Cross, Jacques Lacan and the Contemporary Understanding of Spiritual Direction - Murphy, Mark Gerard (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
"A deeply engaged inquiry into the possibility of mystical spiritual direction today - the true topic of the book is ourselves, our spiritual fate. Furthermore, Murphy ruthlessly analyses how mystical experience is caught in the global capitalist commodification - if you really want an authentic spiritual experience, you should begin with a critique of capitalism." -Professor Slavoj Zizek, International Director of the Birkbeck Institute for the Humanities, UK "Through a powerfully illuminating reading of Jacques Lacan's 'anti-experientialist' psychoanalytic practice, Murphy uncovers the cultural forces which reduce spirituality to superficial notions of wellbeing." -Dr Edward Howells, Associate Tutor at Ripon College Cuddesdon and Associate Member of Faculty of Theology and Religion, University of Oxford, UK This book examines Lacanian psychoanalysis and Christian mystical theology demonstrating the former's potential for reinvigorating spiritual direction. The author outlines how current methods of spiritual direction become saturated with self-help psycho-pop methodologies, and that desire has therefore been foreclosed in these practices. He suggests that the root of this is a focus on 'positive affective experientialism', which means spiritual direction must focus on emotional wholeness, healing and positivity. Finally, he argues that a new dialogue between John of the Cross (a mystic whose writings on spiritual direction formulate part of the core of the Catholic spiritual tradition) and Jacques Lacan can open the way for a spiritual direction beyond the confines of experientialism. The book concludes that we can only escape the experiential commodification of spiritual direction by critiquing the drive to experience in and of itself. This novel work will appeal in particular to students and scholars of psychoanalysis, religion, philosophy and critical theory. Mark Gerard Murphy is Lecturer at St Mary's University, Gillis Centre, Scotland, where he convenes courses on ethics, philosophy, and mystical theology and spirituality. .
1. Introduction -- Part I The Loss Of Mystical Desire In Christian Spiritual Direction -- 2. The Shift In Spiritual Direction -- 3. Desire In Pre-Modern Spiritual Direction -- Part II Recovering Mystical Desire In Spiritual Direction: A Juanist-Lacanian Approach -- 4. Lacan's Conception Of Psychoanalysis -- 5. Lacan And Spiritual Direction -- 6. The Mystical Speech Of Lacan -- 7. Listening And Speaking In Juanist-Lacanian Spiritual Direction -- 8. Conclusion.
Keywords: Psychoanalysis; Spirituality; Psychology and religion; Philosophy of mind; Theology; Psychoanalysis; Spirituality; Psychology of Religion and Spirituality; Philosophy of Mind; Christian Theology